Honor Killing in Legal, Cultural and Human Rights Perspective - Zenny Rezania Dewantari (Problematika Hukum, 2015)
This paper is talking about honor killing, a form of murder in which the act itself is considered as a necessity. This term is common used to picture a murder of a woman conducted by a man in a patriarchal community, as a retaliation of what she did that’s brought shame to a family. In a broader term, honor killing means a necessary murder by a family member to a victim who is believed to have brought shame to a family.            Motives behind honor killing are what make this killing unique. The motives are commonly to restore the equilibrium after the damage brought by the victim to the family. There are no certain criteria of what damaging behavior is. Victims were usually women with some cases were involving men as a victim.            Right of life is stated in Universal Declaration of Human Rights. Many human rights conventions also state a protection of women’s human rights. So in a human rights perspective, honor killing is against human rights especially right of life and specifically for women, it is against rights of a woman.            Naturally, human rights are universal. Problem occurs when this universality meets local cultures, beliefs, and traditions. Honor killing is sometimes allowed in those certain groups. So it is a challenge of human rights enforcement to get inside the cultures and beliefs of some state’s ideology that might be different with UDHR statements, including honor killing phenomenon.